Pengembangan Sistem Informasi Penerimaan Peserta Didik Baru (PPDB) berbasis Web di Madrasah Aliyah Negeri2 Malang - Miftahul Ulum; Satrio Agung Wicaksono; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Madrasah Aliyah Negeri 2 Malang is an educational institution that provides one of the services in the form of information services in the form of information on new student admissions (PPDB). Acceptance of students is an activity carried out at the end of each academic year in order to find students graduating from junior high school to become students at the school. However, the process of accepting new students at MAN 2 Malang is still done manually. Prospective students must come directly to the school to fill out the registration form in the form of printed paper. Besides that, the input and processing of registration data by officers is also by manual typing, and the difficulty of delivering PPDB information to the public. So based on the difficulties and problems that arise, it is necessary to explore the need for research to develop information systems that can overcome problems in the acceptance of new students (PPDB) with a web base at MAN 2 Malang. This study uses the Software Development Life Cycle (SDLC) waterfall model with its stages. System requirements analysis is carried out by interviewing and observing physical documents on PPDB. The results of interviews and observations were analyzed in order to produce system requirements divided into two actors, namely admin and prospective students. The design of the results of the needs analysis using the Unified Modeling Language (UML) includes use cases, activities, sequences, and class diagrams. The system implementation uses PHP and the Laravel framework as server-side processing that implements MVC. Testing using the black box validation method with 100% valid results. Followed by the UAT test which resulted in 100% of the system being accepted and used by stakeholders.